KCNQ1 Haplotypes Associate with Type 2 Diabetes in Malaysian chinese subjects - Saif-Ali, R.; Ismail, I.S.; Al-Hamodi, Z.; Al-Mekhlafi, H.M.; Siang, L.C.; Alabsi, A.M.; Muniandy, S. (2011)
The aim of this study was to investigate the association of single nucleotide polymorphisms (SNPs) and haplotypes of potassium voltage-gated channel, KQT-like subfamily, member 1 (KCNQ1) with type 2 diabetes (T2D) in Malaysian Chinese subjects. The KCNQ1 SNPs rs2237892, rs2283228 and rs2237895 were genotyped in 300 T2D patients and 230 control subjects without diabetes and metabolic syndrome. Two logistic regression models of analysis were applied, the first adjusted for age and gender while the second adjusted for age, gender and body mass index. The additive genetic analysis showed that adjusting for body mass index (BMI) even strengthened association of rs2237892, rs2283228 and rs2237895 with T2D (OR = 2.0, P = 5.1 x 10(-5); OR = 1.9, P = 5.2 x 10(-5); OR = 1.9, P = 7.8 x 10(-5), respectively). The haplotype TCA containing the allele of rs2237892 (T), rs2283228 (C) and rs2237895 (A) was highly protective against T2D (Second model; OR = 0.17, P = 3.7 x 10(-11)). The KCNQ1 rs2237892 (TT), and the protective haplotype (TCA) were associated with higher beta-cell function (HOMA-B) in normal subjects (P = 0.0002; 0.014, respectively). This study found that KCNQ1 SNPs was associated with T2D susceptibility in Malaysian Chinese subjects. In addition, certain KCNQ1 haplotypes were strongly associated with T2D.